2016
DOI: 10.1103/physreve.93.032307
|View full text |Cite
|
Sign up to set email alerts
|

Collective motion patterns of swarms with delay coupling: Theory and experiment

Abstract: The formation of coherent patterns in swarms of interacting self-propelled autonomous agents is a subject of great interest in a wide range of application areas, ranging from engineering and physics to biology. In this paper, we model and experimentally realize a mixed-reality large-scale swarm of delay-coupled agents. The coupling term is modeled as a delayed communication relay of position. Our analyses, assuming agents communicating over an Erdös-Renyi network, demonstrate the existence of stable coherent p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 44 publications
2
72
1
Order By: Relevance
“…For example, an individual agent of a flock can be slow enough to respond to a signal coming from its neighbour. This causes communication-delay [38,39,40,41]. It has been shown that in presence of a noise induced transition from translatory to rotatory motion of agents [42], the time-delayed communication among them can introduce further instabilities where the harmonically interacting agents can form dynamic clusters or swarms, with a high degree of polarity [38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an individual agent of a flock can be slow enough to respond to a signal coming from its neighbour. This causes communication-delay [38,39,40,41]. It has been shown that in presence of a noise induced transition from translatory to rotatory motion of agents [42], the time-delayed communication among them can introduce further instabilities where the harmonically interacting agents can form dynamic clusters or swarms, with a high degree of polarity [38].…”
Section: Introductionmentioning
confidence: 99%
“…Agent i's opinion is represented by the quantity x i = x i (t) ∈ R d , with d ∈ N the space dimension, which is a function of time t ≥ 0. For many applications in biological and socio-economical systems or control problems (for instance, swarm robotics [11,23]), it is natural to include a time delay in the model reflecting the time needed for each agent to receive information from other agents. We therefore assume that agents' communication takes place subject to a variable delay τ = τ (t) ≥ 0, i.e., agent i with opinion x i (t) receives at time t > 0 the information about the opinion of agent j in the form x j (t − τ (t)).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, such systems involve sharing speed and heading data directly among agents, and are somewhat limited in their dynamics, e.g., to flocking, where consensus forms around a network-wide velocity. On the other hand, physically inspired models, where collective motion emerges from the more basic interplay of position-dependent forces and self-propulsion energy, have typically assumed global, homogeneous, or lattice communication topology [39][40][41][42][43][44][45] . Since the latter class of models derive from basic physical principles, they showcase a broader spectrum of emergent motion patterns, and they can more easily incorporate, e.g., active-matter dynamics 15,43 and collective motion on arbitrary surfaces 46 .…”
Section: Introductionmentioning
confidence: 99%
“…To make progress, we consider a generic system of mobile agents moving under the influence of self-propulsion, friction, and pairwise interaction forces 41,43,47,49 mediated through a network 42,48 . In the absence of interactions, each swarmer will tend to a fixed speed, which balances its self-propulsion and friction but has no preferred direction 46 .…”
Section: Introductionmentioning
confidence: 99%